2009
DOI: 10.1177/1534765608325121
|View full text |Cite
|
Sign up to set email alerts
|

Assessing trauma and traumatic stress via the Internet: Measurement equivalence and participant reactions.

Abstract: Though relatively understudied, trauma exposure and resulting posttraumatic stress symptoms are common in college students. Web-based surveys allow for private, cost-effective, and time-efficient assessment of trauma and its sequelae in this at-risk population. This study examines two issues pertinent to Internet assessment of trauma and posttraumatic stress: (a) the reliability of the Internet compared with paper-and-pencil and interview assessments and (b) the acceptability of this assessment modality to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
1
27
1
1
Order By: Relevance
“…Therefore, our study’s generalizability is limited and results may not represent transgender people throughout the U.S. However, investigators have examined the effect of internet- versus noninternet-based survey research (e.g., in person, paper-and-pencil, phone based sampling) in the U.S. on disclosure rates with respect to sexuality (Hines, Douglas, & Mahmood, 2010; Meyerson & Tryon, 2003), trauma (Read, Farrow, Jaanimagi, & Ouimette, 2008), and substance use (Miller & Sønderlund, 2010; Parks, Pardi, & Bradizza, 2006). Findings have suggested that both internet-and noninternet-based survey research are likely to yield similar responses with respect to quality and rates of disclosure (Germine et al, 2012; Gosling, Vazire, Srivastava, & John, 2004; McMorris et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study’s generalizability is limited and results may not represent transgender people throughout the U.S. However, investigators have examined the effect of internet- versus noninternet-based survey research (e.g., in person, paper-and-pencil, phone based sampling) in the U.S. on disclosure rates with respect to sexuality (Hines, Douglas, & Mahmood, 2010; Meyerson & Tryon, 2003), trauma (Read, Farrow, Jaanimagi, & Ouimette, 2008), and substance use (Miller & Sønderlund, 2010; Parks, Pardi, & Bradizza, 2006). Findings have suggested that both internet-and noninternet-based survey research are likely to yield similar responses with respect to quality and rates of disclosure (Germine et al, 2012; Gosling, Vazire, Srivastava, & John, 2004; McMorris et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Further support for this method of data collection comes from research suggesting that Internet-based trauma surveys are highly correlated with both paper-and-pencil and interview methods, regardless of level of symptomatology (Read, Farrow, Jaanimägi, & Ouimette, 2009), and demonstrate similar psychometric properties (Fortson, Scotti, Del Ben, & Chen, 2006). Moreover, prior focus group recommendations regarding effective trauma research with a Japanese population encouraged utilizing a more anonymous method of disclosure, such as the Internet (Allard, 2009), in light of AV that may hinder disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…Though several studies have documented the extent to which online assessments correspond to other more traditional methods (Gosling et al, 2004; E. T. Miller et al, 2002; Read, Farrow, Jaanimagi, & Ouimette, 2009), there has been less research on participant response styles in web-based survey research and whether these may affect data quality. The present study sheds light on the extent of inconsistent responding in these types of studies and provides a practical strategy for conducting an ad hoc inconsistency analysis that can help to identify and predict inconsistent response patterns.…”
Section: Discussionmentioning
confidence: 99%